Potential of treated sewage sludge as organic fertilizer, and phytoremediation capability of jarak (Ricinus communis L.) - Zainuddin, Nur Aziera (2017)
Treated sewage sludge is generated from municipal wastewater. It has been stabilized by mechanical, biological and chemical treatments but heavy metal contents in this waste materials are still high. Improper disposal of treated sewage sludge can cause soil contamination and contributes to Environmental pollution. It can also affect human health and ecosystem. The objectives of this study are two-fold: The first objective is to determine whether treated sewage sludge can be used as an organic fertilizer. The second objective is to assess the potential of Ricinus communis as a phytoremediator of heavy metals in the sludge. For the greenhouse study, the experiment was laid out a Complete Randomized Design (CRD) with four replications. The growth medium was treated sewage sludge mixed with soil at five different levels mainly T1=100% soil (control), T2=25% treated sewage sludge+75% soil, T3= 50% treated sewage sludge+50% soil, T4= 75% treated sewage sludge + 25% soil and T5=100% treated sewage sludge. Soil samples before planting and at harvest were analyzed for texture, pH, N, P, K, C, and heavy metals (Cd, Cu, Fe, Mn, Pb and Zn) using standard procedures. Results showed that the amount of nutrients increased by increasing the amount of treated sewage sludge for both studies. In the greenhouse trial, there was a significant difference (p≤0.05) in N, P, K and C among plant parts. In the case of N, P and K the highest accumulation was in the leaves followed by stems and roots but for total C the highest was in the roots (41.2%) followed by stems and leaves (40.2% and 39.5%, respectively). The contents of Cd, Cu, Fe, Mn, Pb and Zn in the planting medium before planting were significantly (p≤0.05) different among the different levels of treated sewage sludge and different plant parts. In the field study the experiment was laid out in Complete Randomized Design (CRD) with three replications. The treatments evaluated were: T1= 0kg treated sewage sludge, T2 = 100kg treated sewage sludge, T3 = 150kg treated sewage sludge and T4 = 200kg treated sewage sludge. The area for every plot was 18m2 and the treated sewage sludge were spread and mixed with the soil. Soil pH, total N, P, K, C, and micronutrients (Cd, Cu, Fe, Mn, Pb and Zn) were analyzed using standard procedures. The result showed that application of treated sewage sludge significantly increased the percentage of total N, P, K and C in the soil. The availability of N, P, K and C supplied from treated sewage sludge has improved plant height and total biomass. The highest increment of plant height and total biomass were recorded in treatment T3 with the highest height of 3.18m and 1283.33g for total biomass. This study shows that treated sewage sludge contain high amounts of heavy metals particularly for Cd, Cu, Fe, Mn, Pb and Zn which can cause toxicity to our ecosystem but can be considered as a good source of plant nutrients. For both studies the values of bioconcentration factor (BCF) in all treatments for Cd, Fe, and Pb are less than one but for Cu, Mn and Zn the values are more than 1. This indicates that Ricinus communis is an efficient phtoremediator for Cu, Mn and Zn but not for Cd, Fe, and Pb. In the greenhouse and field studies Translocation factor (TF) of Ricinus communis in all treatments for all heavy metals (Cd, Cu, Fe, Mn, Pb and Zn) are more than one. Based on the BCF and TF values, Ricinus communis is an efficient phytoextractor for Cd, Cu, Fe, Mn, Pb and Zn. This species is also tolerant to high amount of treated sewage sludge and can grow well under this condition. It is recommended that future research should include evaluation of Environmental pollution especially on soil and water. In addition effect of using treated sewage sludge as an organic fertilizer on animal and human health need to be determined. This is because treated sewage sludge also contains heavy metals such as Cd, Cu, Fe, Mn, Pb and Zn which can be detrimental to human and animal health.